HUMAN INACTIVITY IN THE CONTEXT OF SUBJECT’S IDENTITY PROBLEM - Dmytro Yu. Snitko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The subject of article is analyze of essence postmodern understanding of human; finding relationship with personal identity and inactivity; accentuation on existential aspects of this relation; to investigate the alternatives to classical and pluralistic conceptions of subject’s identity. Scientific novelty of received results consists in a discovery of the relationship with human inactivity and personal identity. Results: the author has demonstrated that the conception of the subject and its identity in nowadays is very indeterminate. In particular, we can keep watching some contradiction between the interpretations of the subject as an amount of the identifications and statement as a basic ground of human his Self-being. In the context of this contradiction the author has demonstrate the relation with personal identity and human inactivity. Inactivity had understand how subject’s self-alienation and his self-identification with situational social roles and functions. This self-alienation leading to the perversion of true agency (doing), that must be direct on the own being. Grave cause of human inactivity is personal identity, that obstructing communicative, mental and practical agency. Therefore, how the alternative of classical and pluralistic conceptions of identity is the special form of identity, that ground on the subject’s Selfhood – being-in-world.